Muzium Padi, Kedah - Saidin, Aeni Zuhana; Shaari, Nassiriah; Alwi, Asmidah (2021)
Muzium Padi is dedicated in exhibiting artifacts related to paddy planting that aims to preserve the traditional paddy planting processes and its related tools to the new generations. Muzium Padi is the only museum in Asia region that showcases exhibitions and artifacts related to the traditional paddy planting process. This has become the main reason for Muzium Padi to receive the highest museum visits compared to the other museums under Lembaga Muzium Negeri Kedah (LMNK). People visit the museum with high expectation to view and learn about the traditional paddy planting process and particularly to view the traditional tools that are now abandoned and might be forgotten. Therefore, enhancing this visiting experience is very crucial.